2015
DOI: 10.1007/s00253-015-6920-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of fatty acid synthesis in marine fungus-like protists

Abstract: Thraustochytrids are unicellular fungus-like protists and are well known for their ability to produce interesting nutraceutical compounds. Significant efforts have been made to improve their efficient production of important fatty acids (FAs), mostly by optimizing fermentation conditions and selecting highly productive thraustochytrid strains. Furthermore, noticeable improvements have been made in understanding the mechanism of FA biosynthesis, allowing for a better understanding of how thraustochytrids assemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 98 publications
0
16
0
Order By: Relevance
“…Schizochytrium sp. is noteworthy and considered as a satisfactory alternative to fish oil due to the advantages of fast growth rate and high productivity 6, 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Schizochytrium sp. is noteworthy and considered as a satisfactory alternative to fish oil due to the advantages of fast growth rate and high productivity 6, 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The omega-3 PUFAs, including EPA, DPA, and DHA, are produced by certain strains, e.g., thraustochytrids [78]. Biochemical studies have been performed to characterize the distinct enzymes from the standard PKS pathways, which is ultimately helpful for understanding the underlying biosynthetic mechanisms [79]. These findings revealed that the FAS pathway does not participate in the biosynthesis of DHA in the Aurantiochytrium sp.…”
Section: Transcriptional Responses Of the Pks Pathwaymentioning
confidence: 99%
“…Biochemical studies have been performed to characterize the distinct enzymes from the standard PKS pathways, which is ultimately helpful for understanding the underlying biosynthetic mechanisms [43]. These findings revealed that the FAS pathway does not participate in the biosynthesis of DHA in the Thraustochytriidae sp.…”
Section: Transcriptional Responses Of the Pks Pathwaymentioning
confidence: 99%